Kwestia utworzenia czechosłowackich jednostek wojskowych w Wielkiej Brytanii w początkowym okresie II wojny światowej (wrzesień – grudzień 1939 r.) - Żurawski vel Grajewski, Radosław Paweł (Acta Universitatis Lodziensis. Folia Historica, 2012)
The post-München agreement Czechoslovak political emigration aimed to organise the Czechoslovak army in exile just on the eve of the outbreak WW II. While Štefan Osuský – the Czechoslovak ambassador in Paris was developing the negotiation with French government on the organisation of the Czechoslovak army in France, Edvard Beneš the last president of the First Czechoslovak Republic tried to win the British support for the formation of the Czechoslovak military detachments in Great Britain. Still his main real aim was rather the political and not the military one. By forming the Czechoslovak troops in the United Kingdom he expected to open the way for recognition by the British government the Czechoslovak political representation in exile as a head of those troops (Provisional Government or National Committee). From the British point of view the organisation of the Czechoslovak troops in Great Britain was politically inconvenient and military unimportant. That question could produce the political tensions with Hungary and Italy which were both still out of war in that time. Moreover the British support for the idea of the formation of the Czechoslovak forces in the UK would have been a kind of a commitment to support the reconstruction of the Czechoslovak state thus turning that cause into one of the war aims of the British Empire which British government was not ready to accept in that period of the war. Another aspect of that question is the severe lack of military equipment in disposition of the British authorities who in such a situation decided to deliver it first of all to the British Army and not to the foreign troops. The formation of the Czechoslovak troops was not seen by the British as the real reinforcement of the allied military power, but only as the political act that it was indeed. In such a situation the British government decided to wait for the development of the Czechoslovak-French negotiation concerning the formation of the Czechoslovak army in France, and agreed only to support that process by sending the Czechoslovak conscripts from Great Britain to France. No agreement concerning the formation of the Czechoslovak forces in Great Britain was signed, still it was not excluded as regards the following months of the war.